Improving Handwashing Behavior of School-Age Children Through a Game-Based Educational Program - Fradianto, Ikbal; Andriyanto, Arief; Akbar, Nur; Yulanda, Nita Arisanti; Bahtiar, Bahtiar (ASEAN Journal of Community Engagement, 2022)
Handwashing plays an essential role in overcoming health problems. Washing hands is a straightforward exercise but will not be done if not adequately informed and drilled on it. School-age children are a vulnerable group relative to health problems, but at the same time, is an excellent group to be given appropriate education. Educating school- age children on the importance of washing their hands is critical to improving health behavior. This community-based research aims to increase school-age children’s handwashing knowledge, attitudes, and practices using a game-based educational program. As a result, there are improvements in the handwashing behavior of around a hundred children in Curug Village, Cimanggis Depok, Indonesia, after a twelve- month-long program. This suggests that through appropriate approaches for promoting healthy living behavior to the children, such as a game board, the project can be successful and sustainable.